(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Going by the title of the research, it is purely Institution-based research in nature, as it focuses on the use of familiarity related address terms among academic staff of Jigawa State College of education and Legal Studies Ringim. The objectives of this research are: to study the address terms use in the selected tertiary institution in Jigawa State, examine the sources of address terms use among the academic staff, investigate the reasons and social factors that determine the use of the terms among the academic staff in the tertiary Institution. The study adopts Discourse analysis theory in the analysis of the data and ethnography of communication method for the data collection. The findings of the research reveal four types of familiarity related address terms that are used among academic staff of JSCOELS Ringim. The identified terms are: name, descriptive, honorific and kinship term. Besides, the reasons behind the use of the terms among the academic staff are: to show familiarity, respect, intimacy, politeness and power differential. Similarly, the research findings reveal the existence of four social factors that determine the usage of the terms among the academic staff. Such as: Education, occupational hierarchy, social status, and degree of intimacy. Lastly, the research results show that the academic staff used both English and Hausa familiarity related terms of address in addressing each other.